Fire Emergency Action Plan In The Indonesia Stock Exchange Building - Kuncoro, Lambang; Rivai Zainal, Veithzal; Hakim, Azis (Green Publisher, 2023)
This research is motivated by the curiosity of how far the preparedness of the Fire Emergency Action Plan (FEAP) is managed in the Indonesia Stock Exchange Building with the aim of anticipating a fire emergency, knowing a plan that contains procedures that regulate who should do what in the event of an emergency. emergencies, as well as increasing the alertness of building occupants in dealing with emergency situations and conditions. This study is an observational study with a cross-sectional design. The research was conducted by comparing the data from observations and interviews. The results of the study show that the Fire Emergency Action Plan has been running well in accordance with KepDirjen Kimpraswil No : 58/KPTS/DM/2002 Concerning Technical Instructions for Fire Emergency Action Plans in Buildings. However, it still needs to be improved, especially in the Fire Emergency Action Training.